Iniciativa de crecimiento personal y bienestar subjetivo: el rol mediador del significado en la vida - Freitas, Clarissa Pinto Pizarro; Cankaya, Elif Merve; Damásio, Bruno Figueiredo; Haddad, Emily Jean; Kamei, Helder Hiroki; Tobo, Patricia Renovato; Koller, Sílvia Helena (Acción Psicológica, 2018)
This study investigated the mediating effect of meaning in life on the relationship between personal growth initiative and subjective well-being. The sample was composed of a total of 1,899 Brazilian participants who voluntarily took part in this study by completing the study survey. Based on the results of the structural equation modeling, the relationship between personal growth initiative and subjective well-being was found to be partially mediated by the presence of meaning in life. Age was found to influence the mediation, as older participants reported greater PGI and MIL. Limitations of the study, as well as directions for future research are discussed.